State-of-Charge Estimation of Li-Ion Battery in Electric Vehicles: A Deep Neural Network Approach - How D.N.T.; Hannan M.A.; Lipu M.S.H.; Sahari K.S.M.; Ker P.J.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automotive batteries; Charging (batteries); Deep neural networks; Electric vehicles; Ions; Lithium compounds; Lithium-ion batteries; Neural networks; Ambient environment; Battery chemistries; Crucial parameters; Federal test procedures; State of charge; State-of-charge estimation; Training algorithms; Vehicle applications; Battery management systems